What's eating Gilbert Grape? [videorecording (DVD)] - Depp, Johnny; Lewis, Juliette; Steenburgen, Mary; DiCaprio, Leonardo; Reilly, John C., 1965-; Glover, Crispin; Hedges, Peter (Paramount Pictures, 2006)
American drama film directed by Lasse Hallström. Gilbert lives in Endora, a place where nothing happens. Aside from a secret affair with a housewife, Gilbert spends his days stocking shelves at a grocery store, caring for his mentally handicapped brother, and holding together a large family headed by Mama, a former beauty queen whose weight tops 500 pounds. But just when Gilbert thinks nothing with ever change, a pretty stranger arrives on the scene, capturing Gilbert's heart and inspiring him to make a break.